Juridical Analysis of Protection of the Rights of Indonesian Citizens & Ethnic Rohingya Refugees in Indonesia: A Meta-Analysis Based on Humanitarian and Security Aspects - Salsabila, Alyah Rezky; Farrel Maulana Riyadi (HM Publisher, 2024)
The humanitarian crisis experienced by the Rohingya ethnic group has prompted a massive exodus, including to Indonesia. This research aims to analyze juridically the protection of the rights of Indonesian citizens (WNI) and Rohingya refugees in Indonesia, with a focus on humanitarian and security aspects. The meta-analysis was carried out by reviewing literature from 2018-2024, including scientific journals, government reports, and international legal documents. Qualitative analysis is used to evaluate the protection of the rights of Indonesian citizens and Rohingya refugees based on humanitarian and security principles. The results of the analysis show that there is a gap between the national and international legal framework in protecting the rights of Rohingya refugees in Indonesia. Humanitarian aspects are often ignored in policies that prioritize security aspects. This has a negative impact on the basic rights of Rohingya refugees, such as the right to life, health, education, and work. This research recommends a more comprehensive approach to protecting the rights of Indonesian citizens and Rohingya refugees, by integrating humanitarian and security aspects. Legal and policy reforms are needed to ensure the protection of the rights of Rohingya refugees in line with international standards.